2014
DOI: 10.1002/adsc.201300916
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Selective Semihydrogenation of Terminal Alkynes with Hypophosphorous Acid

Abstract: A novel copper-catalyzed selective semihydrogenation of terminal alkynes using hypophosphorous acid as hydrogen donor took place efficiently to afford the corresponding alkenes in high yields. A broad range of substituted terminal aromatic and aliphatic alkenes, including terminal dienes and enynes bearing internal triple bonds, can be efficiently synthesized by this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Cao's group reported a novel selective semihydrogenation of terminal alkynes, catalyzed by copper in the presence of H 3 PO 2 as hydrogen donor. 11 The reaction took place with high selectivity so that over-reduction products of ethylbenzene were not detected. The employment of fully deuterated hypophosphorous acid (D 3 PO 2 ) showed the distribution of deuterium incorporation in the alkenes.…”
Section: (F) Selective Semihydrogenation Of Terminal Alkynesmentioning
confidence: 99%
“…Cao's group reported a novel selective semihydrogenation of terminal alkynes, catalyzed by copper in the presence of H 3 PO 2 as hydrogen donor. 11 The reaction took place with high selectivity so that over-reduction products of ethylbenzene were not detected. The employment of fully deuterated hypophosphorous acid (D 3 PO 2 ) showed the distribution of deuterium incorporation in the alkenes.…”
Section: (F) Selective Semihydrogenation Of Terminal Alkynesmentioning
confidence: 99%
“…By comparing the performance, the broad scope, and the environmental friendliness of our Pd 0 ‐AmP‐HSN/DMSO system, it can be concluded that it compares favorably to many of the recently developed catalytic protocols for the partial reduction of alkynes. For example, it has the advantage of affording high yields of alkenes under milder reaction conditions, whereas other catalytic systems require higher catalyst loadings, higher H 2 pressures, and elevated reaction temperatures . Particularly noteworthy in this regard is that our catalytic system is comparable in performance to a number of homogenous Pd protocols .…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, Pd 0 ‐AmP‐HSN offers a more straight‐forward separation and recycling of catalyst without any compromise in activity, which is typically seen upon heterogenization. The ability of the current protocol to operate efficiently by using H 2 and DMSO makes it an atom‐efficient and green alternative to other catalytic systems using more environmentally harmful reductants and poisoning agents …”
Section: Resultsmentioning
confidence: 99%
“…In a related process, terminal alkynes 23 (which are not tolerated by the abovementioned protocol based on ammonia borane) could be converted into the corresponding terminal alkenes 24 by employing hypophosphorous acid as the H 2 equivalent, while internal alkynes remained intact (Scheme 4, c). 41 As a much more practical and ready available H 2 equivalent, it was recently shown that iso-propanol can also be employed in copper(I)-catalyzed transfer hydrogenations. 42 With a simple NHC/copper(I) complex 22 in catalytic amounts and NaOtBu as a basic additive, internal alkynes 20 could be converted into Z-alkenes 21 in moderate to very good yield (48-96%), while maintaining a high to excellent Z/E ratio (82:18 to 99:1) (Scheme 4, b).…”
Section: Homogeneous Copper-catalyzed Transfer Hydrogenationsmentioning
confidence: 99%